OIL CONCESSION CONTRACTS (World Bulletin of Management and Law, 2023)
In the name of God, the Most Merciful, the Most Merciful, and by God we seek help, and after praying for the most honorable of creation, our master Muhammad and his good and pure family and companions. After the previous customs and laws apply to many types of contracts, including commercial contracts, including civil contracts, and commercial contracts on which the transportation contract, the agency contract and other commercial contracts are based. For the development of contracts and the intensification of efforts in coordinating and amending them to avoid errors and also for the stability of transactions between people and merchants, many types of contracts have been developed. Among them is the oil concession contract, which was dealt with at the beginning of the twentieth century after the emergence of the socalled oil phenomenon in most of the oil-producing countries in which this wealth was discovered. One of these countries is Iraq, as it is considered the most powerful resource on the international and Gulf level as well, due to the presence of large amounts of wealth that has been blessed with God bless them, including oil, gas and other precious materials. At the beginning of dealing with this oil wealth, there was no regulation of rights and obligations between states, or between states, people, or companies that extract oil, so these companies used to take a large part of the countries to explore, explore and extract oil, and act freely in the lands of that country that agreed to explore. And there was no authority mentioned by the states over these companies, and the situation was like touching the sovereignty of the state, and it could not act in this respect, as the companies are the owners of the largest share of the wealth, and they give the state a small part of these profits. The field of the oil industry is characterized by a high degree of risk and the need for huge capitals to invest in its field, given the importance of these two factors at the economic level of the state, in addition to the importance of oil as a major source of energy in the world and an essential resource in the budget of the host country (the country that owns the land of oil), as well as considerations for its classification. Among the depleting natural resources, the oil industry was the subject of special attention by the legal legislator in all the producing countries, to regulate the legal framework within which the work of searching for and extracting oil is carried out in a way that guarantees the preservation of it as one of the important natural resources in the process of economic development of the producing countries.
Keywords: way; guarantees; attention; important